2013
DOI: 10.1016/j.intimp.2012.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Optimized dosing of a CCR2 antagonist for amplification of vaccine immunity

Abstract: We have recently discovered that inflammatory monocytes recruited to lymph nodes in response to vaccine-induced inflammation can function as potent negative regulators of both humoral and cell-mediated immune responses to vaccination. Monocyte depletion or migration blockade can significantly amplify both antibody titers and cellular immune responses to vaccination with several different antigens in mouse models. Thus, we hypothesized that the use of small molecule CCR2 inhibitors to block monocyte migration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…The systemic administration of RS 504393, a CCR2 antagonist [25], dose dependently inhibits thermal hyperalgesia in mice with either acute or chronic peripheral inflammation. The antihyperalgesic effect evoked by the highest dose assayed of RS 504393 (3 mg/kg) was rather brief reaching its maximum 30 min after administration and completely disappearing in 1 h. However, the repeated administration of this drug every 6 h induced a more maintained antihyperalgesic effect that could rely on its accumulation as previously described with an RS 504393 analog administered with the same schedule [23].…”
Section: Discussionsupporting
confidence: 51%
“…The systemic administration of RS 504393, a CCR2 antagonist [25], dose dependently inhibits thermal hyperalgesia in mice with either acute or chronic peripheral inflammation. The antihyperalgesic effect evoked by the highest dose assayed of RS 504393 (3 mg/kg) was rather brief reaching its maximum 30 min after administration and completely disappearing in 1 h. However, the repeated administration of this drug every 6 h induced a more maintained antihyperalgesic effect that could rely on its accumulation as previously described with an RS 504393 analog administered with the same schedule [23].…”
Section: Discussionsupporting
confidence: 51%
“…INCB3284 had no effects on systolic BP of WTmice in the absence or presence of 2% saline. Blockade of CCR2 by another CCR2-selective antagonist, 25,26 RS102895, also eliminated HS-induced increase in BP but did decrease it to the level of WT mice (Supplemental Figure 2). These results showed that the CCR2-mediated pathway was involved in salt sensitivity and salt-induced hypertension in KL(+/2) mice but not in spontaneous elevation of BP in KL(+/2) mice.…”
Section: Resultsmentioning
confidence: 95%
“…injection [16] to female sm-EAN-affected CCR2 WT mice from days 13 to 17 post-induction for a total of 5 days. Apart from establishing functional relevance of CCR2 signaling following clinically apparent disease, these series of studies were designed to mimic a therapeutic drug trial.…”
Section: Methodsmentioning
confidence: 99%